IMPLEMENTASI EKSTRAKULIKULER PENCAK SILAT PS. GOPSU DALAM MEMBENTUK KARAKTER DISIPLIN DAN PERCAYA DIRI DI SDN SIDOTOPO WETAN IV SURABAYA - Hakim, Arif Rahman; Akhwani, Akhwani; Sunanto, Sunanto; Thamrin, Muhammad (LPPM Institut Pendidikan Nusantara Global, 2023)
Background extracurricular PS Pencak Silat. GOPSU at SDN Sidotopo Wetan IV Surabaya is very popular and in demand by students, as evidenced by the 643 students, all students take part in the extracurricular Pencak Silat PS. GOPSU. In the process, the Pencak Silat extracurricular PS. Aside from being a forum for developing the talents of Pencak Silat extracurricular PS students, GOPSU is also a place for developing talent. GOPSU also helped shape the character of discipline and self-confidence. The purpose of this study was to analyze the implementation of the Pencak Silat PS extracurricular. GOPSU in shaping the character of discipline and self-confidence of students at school. This research method uses a qualitative approach with a descriptive research type. The results showed that the extracurricular Pencak Silat PS. GOPSU has an important role in shaping the disciplinary character of students. This activity trains students to be disciplined in time, action, and practice. Students are taught to arrive on time, not skip classes, obey rules, be polite, and not lie. In addition to the character of discipline, extracurricular Pencak Silat PS. GOPSU also has a positive effect on increasing student self-confidence. Through structured physical and mental exercises, students can overcome fear and gain confidence in facing various challenges. They are also taught to have the courage to practice movements, lead prayers, and participate in events or competitions. Conclusion This study shows that the extracurricular Pencak Silat PS.